GEOMETRY OF THE LINEAR FOLIATIONS IN C2 - Renato Mario Benazic Tomé (Pesquimat, 2014)
In this work, we study the geometric behavior of the solutions of a bidimentional complex ordinary diferential equation. We prove that the geometry of the leaves depend on the position of the eigenvalues in the complex plain and we will give a completely description of these geometry.